Exploring community health workers’ experiences with mHealth - Ntuli, Siphokazi Emmah (Rhodes University, 2026)
Using the theoretical framework of social capital, this study examines the impact of public digital health interventions (mHealth technology) on community health workers (CHWs), with a focus on their experiences and the integration of this technology into their work. A qualitative research approach was employed, involving ten CHWs who participated in in-depth semi-structured interviews. Through the lens of social capital theory, this study argues that mHealth facilitates connections and relationships among CHWs, nurses, the community, and the Department of Health (DoH). Specifically, mHealth has the potential to strengthen coordination among public health structures, bridge networks, and enhance communication. The findings of the study indicate that community health workers (CHWs) are generally positive about using mHealth, although some older participants are less comfortable with the tools than their younger counterparts. Additionally, the study's findings suggest that mHealth strategies can support the Department of Health in achieving the goals outlined in the South African National Digital Health Strategy for 2019–2024. For example, mHealth could be used beyond primary care registration, follow-ups, referrals to health facilities, tracking high-risk patients, and addressing defaulters. This intervention can also support health promotion and disease prevention campaigns, ultimately contributing to better health for all South Africans and helping to address broader primary health care (PHC) challenges.
a case study on digital public health interventions at Ekangala Clinic in Gauteng Province
Keywords: Uncatalogued